Kajian Sanitasi Sekolah Dasar Di Kabupaten Kayong Utara Provinsi Kalimantan Barat - Reza Wahyudi; Nia Febrianti; Murti Juliandari (Fakultas Teknik, 2019)
The sanitation study of the Primary School in Kayong Utara District demands that the Sanitation Risk area be established in the EHRA study. Based on the EHRA study, the classification of risk categories is divided into three which are namely No, Medium, and Very High Risk. The scope of the study area covers the elementary schools and this encompasses 18 high-risk villages from 4 sub-districts. And the total number of primary and secondary schools in the study conducted was thirty-three. This study used a questionnaire method that was provided by the school for self-assessment. The result stated that sanitation was in an unpleasant category and it can be broken down to the provision of handwashing (35.52%), trash temporary shelter (45.44%), drainage channel (43.42) and PHBS education and practice (47.32%).